Bis[1,1′-(1,3-phenylenedimethylene)di(1H-imidazol-3-ium)] β-octamolybdate - Xiao-Dan Wang; Guang-Feng Hou; Ying-Hui Yu; Jin-Sheng Gao (Acta Crystallographica Section E, 2012)
In the title compound, (C14H16N4)2[Mo8O26], the β-octamolybdate anion is centrosymmetric. N—H...O hydrogen bonds link the diimidazolium cations and the polyoxidoanions into a chain structure along [100]. π–π interactions between the imidazole rings and between the imidazole and benzene rings [centroid–centroid distances = 3.611 (2) and 3.689 (3) Å, respectively] connect the chains.